Relation between abnormalities of heamostasis and neoangiogenesis in breast cancer patients - Łojko, Anna; Zawilska, Krystyna; Grodecka-Gazdecka, Sylwia; Komarnicki, Mieczysław (Contemporary Oncology/Współczesna Onkologia, 2006)
Haemostatic abnormalities in cancer patients have been observed for many years and still represent a matter of debate. The hyperactivation of blood coagulation associated with malignancy plays a crucial role in tumour growth, favours tumour spread and is thought to be a first step in formation of new vessels. Haemostasis, angiogenesis and tumour growth are strongly connected with each other in tumour pathogenesis. It seems that vascular-endothelial growth factor (VEGF), the most important proangiogenic cytokine, is also the most important link between activation of haemostasis and angiogenesis in tumour growth. The aim of the study was to investigate the relationship between haemostasis abnormalities and angiogenesis in breast cancer patients. The study group consisted of 79 women suffering from breast cancer with I to IV clinical stage of disease. The control group consisted of 25 age-matched, healthy women. The plasma samples were obtained before starting any medical procedure. The following parameters were measured: platelet count, activated partial thrombin time, prothrombin time, a-antiplasmin activity (a-AP2), and fibrinogen, D-dimer (DD) and VEGF level. A significant correlation was observed between VEGF and DD and between VEGF and fibrinogen plasma levels, the strongest in patients with metastasis disease. In the study group significantly higher fibrinogen, DD and VEGF plasma levels and significantly lower activity of a-2AP were observed. Observed abnormalities were correlated with stage of disease. In patients with breast cancer chronic intravascular coagulation of minor grade with secondary fibrinolysis was observed. These processes were correlated with angiogenesis and with stage of disease, confirming the association between haemostasis disturbances and angiogenesis in tumour growth.